(untitled) (African Journal of Law and Politics, 2023)
The role played by corporate insolvency professionals in the management of difficulties of ailing firms cannot be overemphasized. He is like the centre stage player around whom most of the episodes of the proceedings revolve. The survival or safe exit of the enterprise depends largely on the personality of the expert. In most jurisdictions of the world, this organ is meticulously regulated by law, so that the enterprise in its difficult moments gets the best in terms of ingenuity. Under OHADA and English law, salient changes have been made by the legislator to improve on the performance of corporate rescue professional. This paper compares the relevant features of this organ under these two jurisdictions and the extent to which regulation has improved the legal landscape for general corporate rescue objectives. The laws and court decisions demonstrate a progression in ameliorating the quality of this very important organ. Regulation has tightened the conditions for access to the profession by highlighting accountability, fairness, integrity, independence, responsibility, professional proficiency and skill. A lot has been left in the hands of member states legislation under OHADA law creating room for delay and overturning the harmonisation aspirations of the community legislator. The balance sheet under English law lends credit to a more efficient framework which has been classified by the World Bank as the best in the world. This should inspire amendments to the relevant provisions in this area by the OHADA law maker.